Pegadaian General Company in the Effort of Credit Security and Customer Development - Soleh, Moh.; Wijayanti, Leni Dwi (Budapest International Research and Critics University, 2021)
Pegadaian is a credit institution with a pawn system as a credit institution. Pegadaian distributes loan funds to those in need with relatively low interest and fast service so that the distribution of loan funds is guaranteed and safe, then a pawn system is applied, namely the delivery of movable goods as collateral to the pawnshop, which is equal to or higher than the loan amount. Because every financial institution must be a legal entity, the position of the Pawnshop Service was changed to a State Company based on Law no. 19 of 1960 as the implementation of the Act issued PP no. 178 of 1961 dated May 3, 1961 concerning the Establishment of the State Pawnshop Company. With PP No. 7 of 1969 dated March 11, 1969 the position of the State Pawnshop Company was changed to a Bureau of Firm (Perjan). Bureaucracy Company is a form of State business with legal entity status as regulated in Law no. 9 of 1969. Pegadaian as a business entity also adheres to the business oriented principle, fostering profits for the company is the goal. This is evidenced by the existence of additional business activities in addition to the main business in the field of financing, until now the pawnshop is the only formal institution in Indonesia which based on the law is allowed to conduct financing in the form of lending on the basis of the law of pawning.